2007
DOI: 10.1007/s11832-007-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell Saver: Is it beneficial in scoliosis surgery?

Abstract: Study design Review of the use of Cell Saver in a nonrandomized group of patients undergoing spinal fusion for scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 15 publications
1
35
1
Order By: Relevance
“…9 Only very few studies were performed to assess the benefit of ANH or ICS in scoliosis surgery, and the results were conflicting. [10][11][12][13][14] In this prospective randomized study, we compared the perioperative hemoglobin levels in patients who had both the ANH and ICS technique against those who only had ICS technique during PSF surgery.…”
Section: Introductionmentioning
confidence: 99%
“…9 Only very few studies were performed to assess the benefit of ANH or ICS in scoliosis surgery, and the results were conflicting. [10][11][12][13][14] In this prospective randomized study, we compared the perioperative hemoglobin levels in patients who had both the ANH and ICS technique against those who only had ICS technique during PSF surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers 6 have evaluated the benefit of IBS in surgery for scoliosis comparing two groups; one with 58 patients, in which this method was used, and another with 37 patients in which it was not used. Those authors found that the volume of blood that needs to salvaged by IBS to justify its use in surgery is at least 500 ml.…”
Section: Discussionmentioning
confidence: 99%
“…At our and other institutions, at least 250 cc of blood must be collected to wash and process the blood for approximately a third of its return to the patient. There has been controversy regarding its "added value" [12][13][14] due to these minimum blood loss requirements, as well as inconsistencies in reports on cell saver reducing the rate of transfusion. However, these studies referred to more limited lumbar procedures, in contrast to the more extensive posterior spinal fusion performed in our series of scoliosis cases, which involved an average of 11.5 levels and longer operative times with higher risk of increased blood loss, in a population in which blood transfusion was not an option.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the study population was 15 years (range, [12][13][14][15][16][17][18][19][20][21]. This included five males and five females.…”
Section: Patient Variablesmentioning
confidence: 99%
See 1 more Smart Citation